MORPHOLOGICAL INDICATORS OF PRIMARY COWS OF DIFFERENT GENOTYPES - Kadralieva, B. T.; Kosilov, V. I.; Кадралиева, Б. Т. (ЗКАТУ им. Жангир хана, 2023)
The article presents the results of studies of morphological parameters of blood, mineral and protein composition in the blood serum of first-calf cows. The effect of the genotype on both the number of red blood cells and the hemoglobin content in the blood has been established. The effect of the genotype on both the number of red blood cells and the hemoglobin content in the blood has been established. At the same time, the first-calf cows of the black-and-white breed of group I differed by the minimum value of the analyzed indicators. So they lost to the Holstein crickets of the German selection of group II in terms of the number of red blood cells in the blood in winter by 0.33*1012/l (4.73% P<0.01), in summer – by 0.45*1012/l (6.24%, P<0.01), the hemoglobin content, respectively, by 2.47 g/l (2.13%, p<0.05) and 2.95 g/l (2.52%, p<0.05), holsteins of the Dutch selection of group II – by 0.46*1012/l (6.60%, p<0.01) and 0.68*1012/l (9.43%, p<0.01), 3.42 g/l (2.95%, P<0.01) and 3.25 g/l (2.78%, P<0.01), by crossbreeds of group IV– 0,18*1012/ l (2.58%, P < 0.05) and 0.09 * 1012/l (1.25%, P > 0.05), 1.40 g/l (1.21%, P < 0.05) and 1.92 g/l (1.64%, P < 0.05), by crossbreeds of group V – 0.24*1012/l (3.44%, P<0.05) and 0.32*1012/l (4.44%, P<0.05), 2.16 g/l (1.86%, P<0.01) and 2.40 g/l (2.05%, P<0.05). The minimum value of the analyzed indicators was distinguished by the first-calf cows of the black-and-white breed. They were inferior to the Holstein peers of the German selection in terms of the number of red blood cells in the blood in winter by 0.33 · 1012/l, in summer – by 0.45 · 1012/l; according to the hemoglobin content – by 2.47 g/l and 2.95 g/l, respectively, Dutch holsteins – by 0.46 ·1012/l and 0.68 · 1012/l, 3.42 g/l and 3.25 g/l, crossbreeds ½ holsteins of German selection × ½ blackand-white – 0,18· 1012/ l and 0.09 · 1012/l, 1.40 g/l and 1.92 g/l, crossbreeds ½ holstein Dutch selection × ½ black and mottled – 0,24 · 1012/ l and 0.32 · 1012/l, 2.16 g/l and 2.40 g/l. The effect of the genotype on the albumin content in the blood serum of first-calf cows has been established. At the same time, their maximum level was distinguished by animals of the Holstein breed of foreign selection of groups II and III, the purebred first–born cows of the black–and-white breed of group I, crossbreeds of groups IV and V were characterized by intermediate inheritance of the trait. Suffice it to note that the first-born cows of the black-and-white breed of group I were inferior to their peers of groups II, III, IV and V in terms of serum albumin concentration in winter, respectively, by 1.26 g/l (3.12%, P<0.01), 1.63 g/l (4.04%, P<0.01), 0.64 g/l (1.58%, P<0.05), 1.40 g/l (3.47%, P<0.05), in the summer season – by 1.00 g/l (2.38%, P<0.05), 1.25 g/l (2.98%, P<0.05), 0.15 g/l (0.36%, P>0.05), 0.90 g/l (2.14%, P<0.05).
Kadralieva, B. T. MORPHOLOGICAL INDICATORS OF PRIMARY COWS OF DIFFERENT GENOTYPES / B. T. Kadralieva, V. I. Kosilov, Б. Т. Кадралиева. - Текст : непосредственный // Ғылым және білім=Наука и образование=Science and education. - 2023. - № 3-2 (72). Ч. ІІ. - Р. 172-187 (Uralsk). - ISSN 2305-9397
Keywords: black-and-white breed; holsteins of German and Dutch breeding; morphological composition of blood; erythrocytes; leukocytes; vitamin A; dairy cattle breeding; зкату; научный журнал